PERANCANGAN SISTEM INFORMASI LEMBAGA BIMBINGAN BELAJAR LANGUAGE TRAINING CENTER (LTC) DALAM PERSAINGAN ERA GLOBALISASI: Design, Website, Database, System, Information, Students. - Riswan; Nilawati (JURNAL AKADEMIKA, 2023)
Research on the design of information systems for the Language Training Center Tutoring Institute aims to develop a more valid and effective institutional information system for administrative management of course participants. The research procedure was carried out using a waterfall diagram model through the definition phase, namely a field trip to obtain primary data regarding the problems they faced. In the design phase, the researcher designed the database, the form of input, output and interface design, in the implementation phase, the researcher used the PHP and MySQL programming languages to implement what the researcher had designed. And in the testing phase and maintenance phase it aims to determine the level of error and the achievement of the application that has been designed. The Jambi Language Training Center (LTC) Tutoring Institute in the administrative processing of student data from registration to reporting is still done manually. This system causes the administration to be less effective and efficient. For this reason, it is necessary to develop a website-based information system processing in facing business competition in this era of globalization and also to provide excellent service to the community's needs for fast information on this institution. Researchers in designing database applications use Php and Mysql. From this research an interactive website has been produced that can facilitate course institutions in processing student data and also makes it easier for users to obtain information about this institution. This research can be developed by the following researchers in the form of an Android-based application.